2012
DOI: 10.1155/2012/760571
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a Peripheral Residual Cyst: Diagnostic Role of CT Scan

Abstract: The termresidual cystis used most often for retained radicular cyst from teeth that has been removed. Residual cysts are among most common cysts of the jaws. The location of all odontogenic cysts is usually intraosseous. The peripheral (extraosseous) presentations are rare. The peripheral presentation of residual cyst has never been reported in the literature. In this article, the role of CT in diagnosing an unusual peripheral presentation of a residual cyst is discussed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…When the tooth associated with a PC is extracted but the cyst is inadvertently not removed in the same surgical procedure, the remaining lesion is called residual cyst (RC), an entity diagnosed by the association of clinical, radiological and histological features (5,6). The exact pathogenesis of RC and the proliferative capacity of its epithelium are not well-established and it is still a matter of debate if these cysts continue to grow after removal of the associated tooth, if they stop growing or if they can show regression.…”
Section: Introductionmentioning
confidence: 99%
“…When the tooth associated with a PC is extracted but the cyst is inadvertently not removed in the same surgical procedure, the remaining lesion is called residual cyst (RC), an entity diagnosed by the association of clinical, radiological and histological features (5,6). The exact pathogenesis of RC and the proliferative capacity of its epithelium are not well-established and it is still a matter of debate if these cysts continue to grow after removal of the associated tooth, if they stop growing or if they can show regression.…”
Section: Introductionmentioning
confidence: 99%
“…Radiographs generally show a circumscribed, unilocular, welldefined area of radiolucency overlapping the edentulous region. 7,8 In 2015, Sukegawa et al reported that odontogenic cysts can produce carcinomatous changes, with residual cyst being one of the few that can have a malignant transformation. This is because odontogenic cysts result from epithelial lining, which has the potential to transform various types of odontogenic cysts into malignant tumors, but this happens on rare occasions.…”
Section: Discussionmentioning
confidence: 99%
“…The residual cyst occurs due to incomplete surgical removal of a tooth or root with apical periodontitis. [1][2][3][4][5][6] Incomplete removal or non-removal of the periapical lesion can lead to the formation of a residual cyst over time. After a few years, the cyst size can regress, remain unchanged or increase.…”
Section: Discussionmentioning
confidence: 99%
“…When a radicular cyst is not removed after extraction of a tooth with apical periodontitis, the remaining lesion within the maxillar or mandibular bones configure the residual cyst. [1][2][3][4][5][6] They are asymptomatic, most commonly found in the maxilla and represent about 10% of the odontogenic cysts. 1,5 Treatment selection depends on the cyst size and location and may involve curettage, enucleation or endoscopic surgery in cases extended into the maxillary sinus.…”
Section: Introductionmentioning
confidence: 99%